A new species of the coral-symbiont crab genus Cymo de Haan, 1833 (Decapoda, Brachyura, Xanthidae) from Nansha Islands, the South China Sea - Yuan, Zi-Ming; Jiang, Wei; Sha, Zhong-Li (Zootaxa, 2023)
A new species of coral-symbiont crab, Cymo mazu sp. nov., is described from the Nansha Islands in the South China Sea. The new species is distinguished from its congeners by several unique morphological characteristics, including a smooth carapace armed with isolated spiny granules, chelipeds featuring large spines and granules, and a strongly concave endopodite of the first maxilliped. Molecular analysis using mitochondrial cytochrome oxidase I DNA barcodes provides further support for the identification of the new species. The relationships between the new species and its congeners were elucidated through a combination of morphological and molecular evidence. Diagnostic characteristics for differentiation among species of Cymo are discussed, and an updated key to the species of the genus is provided.